Using human induced pluripotent stem cells to reveal astrocyte-neuron interactions in health and disease - Hedegaard, A (2019)
Interactions between neurons and astrocytes underpin normal brain function. Astrocytes fulfil a variety of essential roles, including regulating synapse formation and maintenance, clearing neurotransmitters, and providing homeostatic regulation of the extracellular ionic environment. Evidence for a more active participation is also emerging, in which astrocytes respond to neuronal signals by influencing synaptic strength through gliotransmission. Most of our knowledge regarding neuron-astrocyte interactions stems from animal models, which have been important in dissecting events at a cellular and molecular level. Yet a major question for experimental neuroscience and drug development is how well findings translate from rodents to the human condition. The recent developments in induced pluripotent stem cell (iPSC) technology are providing a valuable tool with which to answer this question. Furthermore, because iPSCs can be derived from clinically diagnosed patients, this technology affords exciting new opportunities to model human disease processes.